주제 중심 융합교양교육을 위한 큐레이션 기반 학습 모형 개발 - 허혜연(Hye-Yeon Huh); 한정규(Jeong-Gyu Han) (교양교육연구, 2024)
이 연구에서는 큐레이션 기반 학습 모형을 개발하고, 이를 학생들의 융합역량을 증진시키기 위한교양 교육적 도구로 활용하는 방안을 모색하였다. 연구 결과, 큐레이션 기반 학습 모형을 개발하였고이는 탐구하기, 정교화하기, 확장하기, 과정 포괄하기의 4단계로 구성되었으며, 각 단계별로 세부 활동을명확히 제시하였다. 전문가 검토 및 타당화 과정을 통해 모형의 적합성 및 유용성을 검증하였으며,최종적으로 개발된 모형은 교육 현장에서 실질적으로 적용 가능한 형태로 완성되었고, 학습전략 또한제시하였다. 이 모형을 교양 교육에 적용한다면, 교양 교육에서 학생들이 한 가지 주제에 대한 다각적시선, 디지털 도구의 활용과 가치에 대한 실천적 지식을 함양시킬 수 있다. 나아가 학생들에게는 낯설고예술의 영역으로 한정되었다는 인식이 있는 전시를 기획하는 경험은 학생들이 스스로 계획을 수립하고실행하며 평가하는 등 자기주도적으로 활동하고, 자신들의 아이디어를 실현하고 성과를 거두며 창조적자신감을 기를 수 있을 것으로 예상된다. 교양교육에서 다양한 주제 중심 학습, 다양한 교수학습 방법을활용하여 학생들이 급변하는 미래 사회에 능동적으로 대응할 수 있는 역량을 기를 수 있도록 해야할것이다. This study sought to develop a curation-based learning model and utilize it as a liberal arts pedagogical tool to enhancestudents' interdisciplinary competencies. As a result, the curation-based learning model was organized into four phases: exploring,elaborating, extending, and encompassing the process, with detailed activities clearly presented for each phase. Expert reviewand validation were conducted to verify the appropriateness and usefulness of the model, and the final model was developedin a form that can be practically applied in the classroom. When applied to liberal arts education, the model can help studentsdevelop a multidisciplinary perspective on a topic, collaboration with other majors, and practical knowledge of the use andvalue of digital tools. Furthermore, the experience of curating an exhibition, which is unfamiliar to students and perceivedto be limited to the realm of the arts, is expected to encourage students to be self-directed in planning, executing, andevaluating their own work, and to develop creative confidence by realizing their ideas and achieving results. Liberal artseducation should utilize a variety of subject-centered learning and various teaching and learning methods to help studentsdevelop the ability to actively respond to the rapidly changing future society. KCI Citation Count: 0